Analisis Penerapan Pembayaran Menggunakan Metode QRIS Terhadap UMKM (Studi Kasus Pada Usaha Minuman Teguk) - Citra Mediana, Alya; Rahmawati, Elma; Untung Mane, Margaretha; Amelia, Revika; Eka Ardiana, Novia (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the implementation of payments using the Quick Response Code Indonesian Standard (QRIS) method in Micro, Small, and Medium Enterprises (MSMEs), focusing on a case study of the Teguk beverage business. The research employs a qualitative descriptive approach, with data collected through interviews and documentation involving employees and customers of the Teguk beverage business. The findings indicate that the adoption of QRIS payments has a significantly positive impact on the efficiency and effectiveness of transaction processes within the Teguk beverage business. Employees reported that using QRIS simplifies transactions compared to cash, resolves issues related to providing change, and allows for real-time transaction monitoring. Similarly, consumers have experienced benefits, with the majority indicating that QRIS makes the payment process faster, more practical, and more efficient. They appreciate the convenience of QRIS, which eliminates the need to carry large amounts of cash and accelerates transactions.